Phase II study of erlotinib and docetaxel with concurrent intensity‐modulated radiotherapy in locally advanced head and neck squamous cell carcinoma. (26th February 2016) - Yao, Min; Woods, Charles; Lavertu, Pierre; Fu, Pingfu; Gibson, Michael; Rezaee, Rod; Zender, Chad; Wasman, Jay; Sharma, Neelesh; Machtay, Mitchell; Savvides, Panayiotis
Abstract: Background: The purpose of this study was to establish the efficacy and toxicities of concurrent erlotinib and docetaxel with intensity‐modulated radiotherapy (IMRT) for locally advanced head and neck squamous cell carcinoma (HNSCC). Methods: Patients received daily erlotinib for 2 weeks, followed by daily IMRT with concurrent weekly docetaxel and daily erlotinib, followed by daily erlotinib for up to 2 years. The primary objective was disease‐free survival (DFS). Secondary objectives included overall survival (OS), patterns of failure, and toxicities. Forty‐three patients were recruited for this study. Results: With a median follow‐up of 48.7 months, the 3‐year DFS, OS, locoregional failure‐free survival, and distant metastasis‐free survival was 69.5%, 81%, 82.4%, and 83.7%, respectively. The most common grade III/IV local toxicities were dysphagia, dermatitis, and mucositis. Patients with p16‐positive tumors had significantly better outcomes. Conclusion: The regimen is tolerable and effective. It is worthy of further investigation in selected patients and may be useful in patients who cannot tolerate cisplatin. © 2016 Wiley Periodicals, Inc. Head Neck 38 : E1770–E1776, 2016